Geochemical Characterization The Waters Of Foggaras The Continental Intercalary Aquifer Of Timinoune Region (south West Algeria) - Benaricha, B.; Khaldi, A.; Elouissi, A.; Mouassa, S.; Zaagane, M. (University of Eloued جامعة الوادي, 2017)
The study of the Continental Intercalary (C.I) groundwater of the region of Timimoune (southwestern Algeria), based on physico-chemical data (major elements), allowed to understand the geochemistry of foggaras water. The aquifer is contained in the formations of the Lower Cretaceous (Albian and Barremian). The waters are strongly mineralized with an average value 2g / l.The waters have a clear predominance of facies chlorinated-sodium. The risk is high to excessive soil salinization, and the risk of medium alkalinity to very high. Statistical analysis led us to reach two conclusions, the first is that, variable electrical conductivity (EC), dry residue (RS), Na+, Ca2+, Cl-, SO4--, mineralization, are best correlated and responsible the signing of the mineral load of water, the second is that the nitrate ion (NO3-) opposite to the above-mentioned variables mark its anthropogenic origin.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 01
Keywords: Continental Intercalary, mineralization, salinity, PCA, Nitrate.